Modification of Clamping System Designated for Automatic Workpiece Exchange - Kandera, Matej; Císar, Miroslav; Kuric, Ivan (Manufacturing Technology Journal, 2019)
Automatic workpiece exchange is one of the important parts of every flexible manufacturing system. This part largely allows complete automation of the component's production cycle. It also greatly contributes to a significant reduction in the workpiece clamping times and contribute to a reduction in the downtime during the machining process. It also allows eliminating a human factor from the production process, thereby contributing to greater machine utilization and higher machining productivity. This article describes certain modifications of interchangeable pallet system designated for specific training CNC machine tool EMCO Concept Mill 105 situated in the laboratory at the Department of Automation and Production Systems. This machine has considerably limited workspace and length of feeds which are the most limiting parameters during design. Mentioned modifications allow manipulating with designed pallets with the industrial robot or special manipulator instead of previously designed manual handling.
Keywords: workpiece exchange; interchangeable pallets; quick-charge pallet system